밀폐 박스거더형 무도장 내후성강 교량의 부식취약부에 대한 방식대책 연구(2) - 송창영; Chang Young Song; 이의호; Eui Ho Lee; 이제현; Jea Hyun Lee; 박현출; Hyun Chul Park; 최재석; Jae Suk Choi; 노영태; Young Tae Noh (Corrosion science and technology, 2013)
This study is the second stage of developing the corrosion control technical manual about unpainted weathering steel bridge with closed box girder structures. This paper contains selection of corrosive sealant to apply into crevice of upper flange, injecting test of sealant at mock-up equipment with various condition, evaluation of experiment result. Through the experiment of injection of sealants into crevice of mock-up equipment, it is proved that the tar sealant injecting corrosion control method is useful to protect corrosion at box girder upper flange corroded by remaning rain water with calcium chloride.